Inovasi “Labu Joy” dalam Pemberdayaan Ekonomi Masyarakat Melalui Diversifikasi Olahan Nugget Labu - Lenny Amelia HK Amelia; Bahmid I Magi; Rista Ade Liana Liana; Muhammad Ilyas Salim Salim (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
Margaluyu Village is an area with high potential for chayote farming, with an agricultural land area of 470 hectares, accounting for approximately 54.638% of the total village area. However, farmers frequently face a severe issue of seasonal surplus, causing the selling price to plummet to Rp 2,500/kg. Furthermore, chayote spoils quickly after harvest, and the community lacks the skills to process the harvest into value-added products. This activity aims to optimize local potential through product diversification innovation in the form of chayote nuggets named "Labu Joy". The method utilized is Community-Based Participatory Research (CBPR). As a result, the community acquired new knowledge, became capable of producing value-added products, and showed higher enthusiasm for developing local food-based enterprises. This innovation has the potential to increase income and strengthen the village's economy.